2016
DOI: 10.1016/j.ijcha.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of subjective health status 10 years post-PCI

Abstract: BackgroundSubjective health status is an increasingly important parameter to assess the effect of percutaneous coronary intervention (PCI) in clinical practice.Aim of this study was to determine medical and psychosocial predictors of poor subjective health status over a 10 years' post-PCI period.MethodsWe included a series of consecutive PCI patients (n = 573) as part of the RESEARCH registry, a Dutch single-center retrospective cohort study.ResultsThese patients completed the 36-item Short-Form Health Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…At the 3-year follow-up after PCI, the significant independent determinants of a lower QoL included the female sex, age >60 years and diabetes mellitus [ 16 ]. According to van den Berge et al, [ 42 ] studies including a 12-month follow-up have shown that age, the male gender, renal impairment, smoking and prior coronary artery bypass grafting were predictors of health status post-PCI. At 10 years post-PCI, the SF-36 scores at baseline, age and previous PCI were significant predictors of subjective health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 3-year follow-up after PCI, the significant independent determinants of a lower QoL included the female sex, age >60 years and diabetes mellitus [ 16 ]. According to van den Berge et al, [ 42 ] studies including a 12-month follow-up have shown that age, the male gender, renal impairment, smoking and prior coronary artery bypass grafting were predictors of health status post-PCI. At 10 years post-PCI, the SF-36 scores at baseline, age and previous PCI were significant predictors of subjective health status.…”
Section: Discussionmentioning
confidence: 99%
“…At 10 years post-PCI, the SF-36 scores at baseline, age and previous PCI were significant predictors of subjective health status. Evaluating the QoL at baseline is a useful indicator to predict the long-term subjective health status [ 42 ]. Modification of the SF-36 score is a key challenge for clinicians involved in the care of PCI.…”
Section: Discussionmentioning
confidence: 99%
“…По данным J.C. Van den Berge и соавт., которые опросили 1055 больных ИБС с помощью опросника SF-36 через 6 мес. после чрескожной транслюминальной коронарной ангиопластики, пожилой возраст и предшествующая реваскуляризация миокарда негативно влияют на физические и ментальные параметры качества жизни [21]. В нашей работе у пациентов, перенесших ОКС, чрескожная транслюминальная коронарная ангиопластика в анам-незе повлияла только на психологический аспект здоровья в отдаленном периоде после реваскуляризации миокарда.…”
Section: Discussionunclassified
“…Restenosis (RS) is an important factor restricting the long-term development of PCI [2,3]. The pathological pro-cess of restenosis involves many factors and multiple pathways; still, the exact mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%